Paying people who use illicit substances or 'peers' participating in community-based work: a narrative review of the literature. (2nd November 2019) - Greer, Alissa Merielle; Pauly, Bernadette; Scott, Alex; Martin, Ruth; Burmeister, Charlene; Buxton, Jane
Abstract: People who use illicit substances that use their lived experience to inform their work, or 'peers, ' are increasingly hired in community-based work internationally. However, this group is disproportionately affected by stigma and discrimination that contributes to inequitable compensation of their work. A narrative review of the literature was conducted to highlight issues involved in compensating people who use drugs who are involved in peer work. After identifying and reviewing over 500 articles, the key issues identified included perspectives of compensation, valuation of participation, type of peer roles, mode of compensation, and structural barriers. How peers' knowledge, roles, and efforts are viewed and therefore valued in our society largely determines the decision to pay and how much to pay people who use drugs. However, some peers also face systemic and contextual barriers, such as local norms, financial exclusion, and a lack of standards that make them susceptible to inequitable pay. This review serves as both a catalyst to promote dialogue around paying peers, and a starting point for approaching the diverse complexities associated with equitable compensation for peer work.